How Sherlock pulled the trick : spiritualism and the pseudoscientific method - McCuskey, Brian, 1967- (The Pennsylvania State University Press, 2021)
"Reconsiders Sherlock Holmes in light of Arthur Conan Doyle's spiritualism. Brings together literary study and author biography to return the iconic Holmes to his mystical origins"--